Distinct neural networks of emotional valence and uncertainty in the human amygdala underlying different mental disorders - Shitong Xiang; Chao Xie; Xiao Xiao; Tobias Banaschewski; Gareth J. Barker; Arun L.W. Bokde; Herta Flor; Antoine Grigis; Hugh Garavan; Penny Gowland; Andreas Heinz; Rüdiger Brühl; et al. (Science Bulletin, 2025)

Characterising differences between self-reported and wastewater-identified drug use at two consecutive years of an Australian music festival - Cheneal Puljević; Benjamin Tscharke; Ellen Leslie Wessel; Cameron Francis; Rory Verhagen; Jake W. O'Brien; Richard Bade; Dhayaalini Nadarajan; Fiona Measham; M.J. Stowe; Timothy Piatkowski; Jason Ferris; et al. (Science of The Total Environment, 2024)

Grazing management for soil carbon in Australia: A review - Sarah E. McDonald; Warwick Badgery; Simon Clarendon; Susan Orgill; Katrina Sinclair; Rachelle Meyer; Dominique Bowen Butchart; Richard Eckard; David Rowlings; Peter Grace; Natalie Doran-Browne; Steven Harden; et al. (Journal of Environmental Management, 2023)

Saturn’s atmospheric response to the large influx of ring material inferred from Cassini INMS measurements - Julianne I. Moses; Zarah L. Brown; Tommi T. Koskinen; Leigh N. Fletcher; Joseph Serigano; Sandrine Guerlet; Luke Moore; J. Hunter Waite; Lotfi Ben-Jaffel; Marina Galand; Joshua M. Chadney; Sarah M. Hörst; et al. (Icarus, 2023)

Advances in cytomegalovirus (CMV) biology and its relationship to health, diseases, and aging - Janko Nikolich-Žugich; Luka Čicin-Šain; Donna Collins-McMillen; Sarah Jackson; Annette Oxenius; John Sinclair; Christopher Snyder; Mark Wills; Niels Lemmermann (GeroScience, 2020)

A framework for predicting which non-native individuals and species will enter, survive, and exit human-mediated transport - James S. Sinclair; Julie L. Lockwood; Sarah Hasnain; Phillip Cassey; Shelley E. Arnott (Biological Invasions, 2020)

Benthic macroinvertebrate communities in five rivers of the Coastal Hudson Bay Lowland - F. Chris Jones; Sarah Sinclair; Wendel Keller (Polar Biology, 2014)

Asynchronous food‐web pathways could buffer the response of Serengeti predators to El Niño Southern Oscillation - A. R. E. Sinclair; Kristine L. Metzger; John M. Fryxell; Craig Packer; Andrea E. Byrom; Meggan E. Craft; Katie Hampson; Tiziana Lembo; Sarah M. Durant; Guy J. Forrester; John Bukombe; John Mchetto; et al. (Ecology, 2013)
Understanding how entire ecosystems maintain stability in the face of climatic and human disturbance is one of the most fundamental challenges in ecology. Theory suggests that a crucial factor determining the degree of ecosystem stability is simply the degree of synchrony with which different species in ecological food webs respond to environmental stochasticity. Ecosystems in which all food‐web pathways are affected similarly by external disturbance should amplify variability in top carnivore abundance over time due to population interactions, whereas ecosystems in which a large fraction of pathways are nonresponsive or even inversely responsive to external disturbance will have more constant levels of abundance at upper trophic levels. To test the mechanism underlying this hypothesis, we used over half a century of demographic data for multiple species in the Serengeti (Tanzania) ecosystem to measure the degree of synchrony to variation imposed by an external environmental driver, the El Niño Southern Oscillation (ENSO). ENSO effects were mediated largely via changes in dry‐season vs. wet‐season rainfall and consequent changes in vegetation availability, propagating via bottom‐up effects to higher levels of the Serengeti food web to influence herbivores, predators and parasites. Some species in the Serengeti food web responded to the influence of ENSO in opposite ways, whereas other species were insensitive to variation in ENSO. Although far from conclusive, our results suggest that a diffuse mixture of herbivore responses could help buffer top carnivores, such as Serengeti lions, from variability in climate. Future global climate changes that favor some pathways over others, however, could alter the effectiveness of such processes in the future.